Optimalisasi Pemanfaatan Sampah sebagai Sumber Nilai Ekonomi Berkelanjutan dalam Perspektif Ekonomi Islam - Lavlimatria Esya; Bahtiar Usman; Ida Busnetty; Muhammad Fadhil Farkhurrohman; Arif Rizki Kusuma (Universitas Pahlawan Tuanku Tambusai, 2026)
This Community Service (PkM) activity aims to analyze the optimization of waste utilization as a source of sustainable economic value from an Islamic economic perspective. This study was conducted on the community of Puri Hutama Housing in East Bekasi who face problems of low awareness of waste sorting, suboptimal waste bank management, and limitations in the development of recycling-based businesses. The method of implementing the activity included a needs survey, module preparation, face-to-face training and counseling, interactive discussions, and evaluation through questionnaires of 25 respondents. The results showed a significant increase in people's understanding and motivation, with 96% of respondents stating that the material was easy to understand and 92% realizing the importance of environmental management from an Islamic perspective. From an Islamic economic perspective, the use of waste is not only economically valuable but also reflects the implementation of the principles of sharia maqashid, especially in protecting the environment (hifdz al-bi'ah) and community welfare (maslahah). Therefore, community-based waste management can be a model of sustainable economic empowerment that is integrative between economic, social, and spiritual aspects.